The Effects of Immigration on U.S. Wages and Rents: A General Equilibrium Approach - Gianmarco I.P. Ottaviano; Giovanni Peri (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2007)
In this paper we document a strong positive correlation of immigration flows with changes in average wages and average house rents for native residents across U.S. states. Instrumental variables estimates reveal that the correlations are compatible with a causal interpretation from immigration to wages and rents of natives. Separating the effects of immigrants on natives of different schooling levels we find positive effects on the wages and rents of highly educated and small effects on the wages (negative) and rents (positive) of less educated. We propose a model where natives and immigrants of three different education levels interact in production in a central district and live in the surrounding region. In equilibrium the inflow of immigrants has a positive productive effect on natives due to complementarities in production as well as a positive competition effect on rents. The model calibrated and simulated with U.S.-states data matches most of the estimated effects of immigrants on wages and rents of natives in the period 1990-2005. This validation suggests the proposed model as a useful tool to evaluate the impacts of alternative immigration scenarios on U.S. wages and rents.
Keywords: F22; J61; R23; 330; Wages; Rents; Housing Prices; U.S. States